Comparison of racemic epi-inosose and (-)-epi-inosose - Krishnaswamy, Shobhana; Patil, Madhuri T.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Crystal Structure Communications, 2011)
The conversion of myo-inositol to epi-inositol can be achieved by the hydride reduction of an intermediate epi-inosose derived from myo-inositol. (-)-epi-Inosose, (I), crystallized in the monoclinic space group P2(1), with two independent molecules in the asymmetric unit [Hosomi et al. (2000). Acta Cryst. C56, e584-e585]. On the other hand, (2RS,3SR,5SR,6SR)epi-inosose, C6H10O6, (II), crystallized in the orthorhombic space group Pca2(1). Interestingly, the conformation of the molecules in the two structures is nearly the same, the only difference being the orientation of the C-3 and C-4 hydroxy H atoms. As a result, the molecular organization achieved mainly through strong O-H center dot center dot center dot O hydrogen bonding in the racemic and homochiral lattices is similar. The compound also follows Wallach's rule, in that the racemic crystals are denser than the optically active form.

Protecting group directed stereoselective reduction of an epi-inosose: efficient synthesis of epi-inositol - Patil, Madhuri T.; Krishnaswamy, Shobhana; Sarmah, Manash P.; Shashidhar, Mysore S. (Tetrahedron Letters, 2011)
A facile and high yielding synthesis of epi-inositol via stereoselective reduction of a pentaprotected epi-inosose is reported. Extent of stereoselectivity during the hydride reduction appears to depend on the ability of the substrate to complex with metal ions in the reducing agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Polyol; reduction; Stereoselective

Orientation of the beta-hydroxyl group controls the diastereoselectivity during the hydride reduction and grignard reaction of inososes - Jagdhane, Rajendra C.; Patil, Madhuri T.; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Tetrahedron, 2013)
A comparison of the results of the Grignard reaction and the hydride reduction of the carbonyl group of epi- and scyllo-inososes reveals that the extent of diastereoselectivity of these reactions is decided by the orientation of the beta-hydroxyl group (or its derivative). Presence of an axial beta-hydroxyl group generally results in the formation of relatively larger amount of the axial alcohol as a result of the reduction of the carbonyl group. The possible reasons for the observed differences in diastereoselectivity between the reactions of these isomeric epi- and scyllo-inososes have been discussed. The sequence of reactions reported here provides convenient access to C-allcylated inositols, such as iso-laminitol and iso-mytilitol as well as 2-O-methyl epi-inositol, an epimer of the naturally occurring ononitol. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; diastereoselectivity; Grignard; Inositol; Nucleophile; reduction

Access to enantiomeric organic compounds with potential for synthesis via racemic conglomerates: inositol derivatives as a case in point - Patil, Nivedita T.; Patil, Madhuri T.; Sarkar, Nitai; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2021)
The crystal structure database was used to identify inositol derivatives that could be crystallizing as racemic conglomerates. Among the six racemic inositol derivatives identified, racemic 4-O-tosyl-6-O-benzyl-myo-inositol-1,3,5-orthoformate (A) was found to be a true conglomerate and was resolved on the multigram scale by the preferential crystallization technique. This resolution procedure does not require the use of any enantiomeric resolving agent. The resolved enantiomers of A are useful for the synthesis of natural and unnatural enantiomeric derivatives of inositol, since they carry orthogonal hydroxy protecting groups. Racemic 4-O-methanesulfonyl-myo-inositol-1,3,5-orthoformate (B) on crystallization from common organic solvents generally yielded racemic twin crystals, while in the presence of structural analogs as additives, they yielded true racemic crystals. A comparison of the crystal structures of the true racemate, twinned crystal and crystal of one of the enantiomers of B, revealed the reasons for the formation of polymorphic (twin) crystals. Such instances are relatively rarely encountered but nevertheless shed light on our understanding of polymorphism and twinning of crystals.

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid